MENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN PREDICT OBSERVE EXPLANATION - Tina Sri Sumartini (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractBased on previous observations note that the ability of some students' mathematical communication is still lacking. Therefore, it is necessary to improve students' mathematical communication ability by using Predict Observe Explanation (POE) learning model. The purpose of this study is to describe the process of implementing mathematics learning through the Predict Observe Explanation (POE) learning model in an effort to improve students' communication skills. The type of this research is Classroom Action Research (PTK) which consists of two cycles and each cycle is done with 4 stages of planning, action implementation, observation, and reflection. The subjects of this study are students of class XI SMK Al Hikmah Garut. The results showed POE learning model can improve students' mathematical communication ability with the learning stages: 1) predict:  predicting the temporary answer of the given mathematical problem; 2) observe: observing other similar issues through teacher demonstrations; 3) explanation: presenting predictions and observations.Keywords: Mathematical Communication Skill, Predict Observe Explanation Learning Model